Les effets des frontières sur les réseaux de marchands et colporteurs alpins (XVIe-XVIIIe siècle) - Laurence Fontaine (Les Cahiers de Framespa)
This article shows, using the example of Alpine merchant migrations, that the border is an actor that affects all aspects of the migrants’ lives. First, it shows that the border is a resource and that migrants know how to play on the differences between the institutions of the various cities and states in order to settle, open depots, and develop their trade. Smuggling is obviously also at the core of their use of the border. The article then highlights how, if war can close borders and stop the flows, armies are always good customers that attract migrant merchants. The last part analyzes the way in which playing with borders transforms the migrants’ ways of life, village relations, as well as their perception of themselves.